Relationship between subjective social status and perceived health among Latin American immigrant women - Mª Visitación Sanchón-Macias; Dolores Prieto-Salceda; Andreu Bover-Bover; Denise Gastaldo (Universidade de São Paulo, 2013)
OBJECTIVE: to explore the relationship between socioeconomic status and subjective social status and explain how subjective social status predicts health in immigrant women. METHODS: cross-sectional study based on data from 371 Latin American women (16-65 years old) from a total of 7,056 registered immigrants accesse through community parthers between 2009-2010. Socioeconomic status was measured through education, income and occupation; subjective social status was measured using the MacArthur Scale, and perceived health, using a Likert scale. RESULTS: a weak correlation between socioeconomic and subjective social status was found. In the bivariate analysis, a significantly higher prevalence of negative perceived health in women with no education, low income, undocumented employment was observed. In the multivariate analysis, higher odds of prevalence of negative perceptions of health in the lower levels of the MacArthur scale were observed. No significant differences with the rest of the variables were found. CONCLUSIONS: the study suggests that subjective social status was a better predictor of health status than the socioeconomic status measurements. Therefore, the use of this measurement may be relevant to the study of health inequalities, particularly in socially disadvantaged groups such as immigrants.